2017
DOI: 10.1371/journal.pone.0182879
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review and meta-analysis of preclinical trials testing anti-toxin therapies for B. anthracis infection: A need for more robust study designs and results

Abstract: BackgroundB. anthracis anti-toxin agents are approved and included in the Strategic National Stockpile based primarily on animal infection trials. However, in the only anthrax outbreak an approved anti-toxin agent was administered in, survival did not differ comparing recipients and non-recipients, although recipients appeared sicker.ObjectiveEmploy a systematic review and meta-analysis to investigate preclinical studies supporting anthrax anti-toxin agents.Data sourcePubMed, EMBASE, and Scopus.Study eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…In the wake of FDA authorizations, the Centers for Disease Control and Prevention (CDC) updated their guidelines for anthrax postexposure prophylaxis and treatment, recommending that antitoxin should be added to antibiotic therapy for any patient suspected of a systemic anthrax infection. Recent closer examination of available clinical and preclinical data has cast doubt upon the beneficial effect afforded by the antibiotics and antitoxin combination in preclinical models (5, 6). Further clinical data collected on the particular form of injectional anthrax during the drug user outbreak in the United Kingdom indicated that death rates did not differ significantly between AIG-IV recipients and nonrecipients (33% versus 21%, with 43 patients included in the study [15 AIG-IV recipients and 28 nonrecipients]), suggesting no benefit of the therapeutics (7).…”
Section: Opinion/hypothesismentioning
confidence: 99%
“…In the wake of FDA authorizations, the Centers for Disease Control and Prevention (CDC) updated their guidelines for anthrax postexposure prophylaxis and treatment, recommending that antitoxin should be added to antibiotic therapy for any patient suspected of a systemic anthrax infection. Recent closer examination of available clinical and preclinical data has cast doubt upon the beneficial effect afforded by the antibiotics and antitoxin combination in preclinical models (5, 6). Further clinical data collected on the particular form of injectional anthrax during the drug user outbreak in the United Kingdom indicated that death rates did not differ significantly between AIG-IV recipients and nonrecipients (33% versus 21%, with 43 patients included in the study [15 AIG-IV recipients and 28 nonrecipients]), suggesting no benefit of the therapeutics (7).…”
Section: Opinion/hypothesismentioning
confidence: 99%
“…Live spore vaccines for human use and cellfree vaccines containing protective antigens are available in various countries (anthrax vaccine adsorbed) for veterinarians, laboratory workers, and others who are likely to be exposed to anthrax. 17…”
Section: Prophylaxismentioning
confidence: 99%
“…By establishing this connection, a rational approach will be ensured that seeks security and quality of life for citizens. Equally, in the globalized world there are possibilities that non-native vectors are unidentified reservoirs of microorganisms altering its life cycle and its pathogenicity, which becomes a new threat to the ecosystems and the human beings who live with them [11].…”
Section: Develop and Implement Guidance Documents Withmentioning
confidence: 99%